2017
DOI: 10.1101/181768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dominance of ST131Escherichia colicarryingblaCTX-Min patients with bloodstream infections caused by cephalosporin-resistant strains in Australia, New Zealand and Singapore: whole genome analysis of isolates from a randomised trial

Abstract: Synopsis/AbstractObjectivesTo characterise multi-drug resistant Escherichia coli isolated from patients in Australia, New Zealand and Singapore with bloodstream infection (BSI).MethodsWe prospectively collected third-generation cephalosporin resistant (3GC-R) E. coli from blood cultures obtained from patients enrolled in a randomised controlled trial. Whole genome sequencing was used to characterise antibiotic resistance genes, sequence types (STs), plasmids and phylogenetic relationships. Antibiotic susceptib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Hospital wound bacterial contamination is a significant issue, especially with surgical operations where the site of a sterile surgery may become contaminated [20,21]. These studies showed that harmful bacteria were present in wounds at significant rates (81.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Hospital wound bacterial contamination is a significant issue, especially with surgical operations where the site of a sterile surgery may become contaminated [20,21]. These studies showed that harmful bacteria were present in wounds at significant rates (81.4%).…”
Section: Discussionmentioning
confidence: 99%